Current and future prospects of “all-organic” nanoinsecticides for agricultural insect pest management - Manna, Sourav; Roy, Sampurna; Dolai, Avishek; Ravula, Arun Reddy; Perumal, Venkatesan; Das, Amlan (Frontiers in Nanotechnology, 2023)
With the popularity of nanotechnology, the use of nanoparticles in pest management has become widespread. Nanoformulated pesticides have several advantages over conventional pesticide formulations, including improved environmental stability, controlled release of active ingredients, increased permeability, targeted delivery, etc. Despite these advantages, recent research shows that several nanoparticles used in conventional nanopesticide formulations can be toxic to crops and beneficial organisms due to bioaccumulation and trophic transfer. Therefore, traditional nanopesticides are thought to be non-advantageous for "green agriculture". In assessing the current situation, developing "all-organic" nanopesticides could be the next-generation weapon for reducing the adverse impact of traditional nanopesticides. However, their formulation and application knowledge is remarkably limited. The green synthesis of "all-organic" nanoparticles makes them more environmentally friendly than conventional nanopesticides due to their minimal residual and hazardous effects. This review focuses on the current development scenario of "all-organic" nanopesticides, their advantages, and potential effects on target organisms compared to traditional nanopesticides.